Pelatihan Teknik Penyelamatan Diri di Perairan dalam Menunjang Keselamatan Pelayaran bagi Masyarakat di Desa Mariana, Banyuasin Palembang - Slamet Prasetyo; Yeti Komalasari; Fitri Masito (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2022)
Considering the enormous risk of work for people who work on ships, skilled, competent, and capable workers are needed to deal with emergency conditions that can cause loss of both property and life. The purpose of this community service activity is to provide education for the community around Mariana Village, Banyuasin Palembang regarding self-rescue techniques in the waters in order to minimize the impact of losses in the form of loss of property and life caused by accidents on board. The method used is training in the form of providing basic competence in self-defense techniques in waters using 4 hours of theory lessons in class and 4 hours of practical lessons in the field (1 lesson = 45 minutes). Overall this training activity went well and smoothly, with an average value of participant satisfaction responding strongly agreeing to 83.14%, a scale of 4 with a very good category (A) as an indicator that the participants' very positive response to the